KECERNAAN DAN EFISIENSI PAKAN PADA OPOSUM LAYANG (PETAURUS BREVICEPS) DI PENANGKARAN - Farida, W. R.; Sulistyowati, Sulistyowati; Sigit, N.; Pratas, R. G. (JURNAL BIOLOGI INDONESIA, 2002)
ABSTRACTDigestibility and Feed Emciency of Flying Squirrel (Petaurus breviceps) in Captivity.Two male flying squirrel (Petaurus breviceps) were used in this experiment to observe feedintake, digestibility and feed efficiency of them. The animals were given alternative diets incaptivity, namely passion fruit, sweet corn, banana, guava, papaya, coconut, sun flower bean,bread, and dogfood. The result showed that average intake of ash, crude protein, ether extract,crude fiber, nitrogen free extract, and gross energy were 2.4%, 2.3%, 9.3%, 6.0%, 69.9%, and4.0 kkallg respectively. The nutrient digestibility coefficient ash, crude protein, ether extract,crude fiber, and nitrogen free extract were 33.6%, 73.5%, 96.2%, 60.9%, and 95,5%respectively. Average body weight gain is 0.35 g/head/week and feed efficiency is 0,4%. Thepreferred feed is bread (58%), sweet corn (l2%), and coconut (1 1 %).Key words: Digestibility, consumption, feed efficiency, Petaurus breviceps